Microwave and Millimeter Wave Technologies from Photonic Bandgap Devices to Antenna and Applications - Minin, Igor (IntechOpen, 2010)
The book deals with modern developments in microwave and millimeter wave technologies, presenting a wide selection of different topics within this interesting area. From a description of the evolution of technological processes for the design of passive functions in milimetre-wave frequency range, to different applications and different materials evaluation, the book offers an extensive view of the current trends in the field. Hopefully the book will attract more interest in microwave and millimeter wave technologies and simulate new ideas on this fascinating subject.